1997
DOI: 10.1007/s004220050329
|View full text |Cite
|
Sign up to set email alerts
|

Human arm stiffness and equilibrium-point trajectory during multi-joint movement

Abstract: By using a newly designed high-performance manipulandum and a new estimation algorithm, we measured human multi-joint arm stiffness parameters during multi-joint point-to-point movements on a horizontal plane. This manipulandum allows us to apply a sufficient perturbation to subject's arm within a brief period during movement. Arm stiffness parameters were reliably estimated using a new algorithm, in which all unknown structural parameters could be estimated independent of arm posture (i.e., constant values un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
337
5
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(375 citation statements)
references
References 40 publications
32
337
5
1
Order By: Relevance
“…This is similar to the approach taken by Dolan (1991) and Gomi and Kawato (1997). However, the approach suffers from uncertainties about the lengths of the links and non-rigidity of the muscle mass.…”
Section: Methodological Considerationsmentioning
confidence: 56%
See 1 more Smart Citation
“…This is similar to the approach taken by Dolan (1991) and Gomi and Kawato (1997). However, the approach suffers from uncertainties about the lengths of the links and non-rigidity of the muscle mass.…”
Section: Methodological Considerationsmentioning
confidence: 56%
“…A number of previous reports have estimated human arm impedance during multi-joint voluntary movements (Gomi and Kawato 1997;Gomi and Osu 1998;Dolan et al 1993;Lacquaniti et al 1993). In these works, small perturbations were applied to the limb and the restoring forces were approximated as a function of displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Katayama & Kawato (1993) and then Gomi & Kawato (1997) repeated Flash's simulation using lower values of sti¡ness and found, not surprisingly, that in order to reproduce the actual trajectory of the hand, the virtual trajectory had to follow a much more complicated pathway. The results obtained by Gomi & Kawato are at variance with those of Won & Hogan (1995), who were able to show that for relatively slow and low-amplitude arm trajectories the virtual equilibrium point was close to the actual trajectory.…”
Section: The Equilibrium-point Hypothesismentioning
confidence: 99%
“…In the context of human arm movements, PCA has been applied to the analysis of rhythmic juggling movements (Post, Daffertshofer, & Beek, 2000), object retrieval (Sabatini, 2002), and whole body reaching movements (Thomas, Corcos, & Hasan, 2005). Many studies use a setup related to the common "center-out task" (Galloway & Koshland, 2002;Gomi & Kawato, 1997;Morasso, 1981), in which participants are instructed to execute relatively slow, well-planned pointing or reach-to-grasp movements constrained to a horizontal plane. Sabatini (2002) found that such planar movements are effected by two types of muscle activity patterns, one for the outward and one for the inward part of the movement.…”
Section: Introductionmentioning
confidence: 99%